Individual lifetime benefit from low-dose colchicine in chronic coronary artery disease patients. (3rd October 2022) - Burger, P; Dorresteijn, J; Fiolet, A; Koudstaal, S; Eikelboom, J; Nidorf, S; Thompson, P; Cornel, J; Budgeon, C; Steg, P; Cramer, M; Teraa, M; et al.
Abstract: Background: Low-dose colchicine reduces the risk of cardiovascular events in patients with chronic coronary artery disease (CAD), but the absolute benefit may vary between patients. Individual benefit from preventive therapies can be estimated using the guideline-recommended SMART-REACH model. Purpose: This study aimed to assess the range of individual absolute 10-year and lifetime benefit from low-dose colchicine according to patient risk profile. Methods: The SMART-REACH model was combined with the relative treatment effect of low-dose colchicine, and applied to all participants from the LoDoCo2 trial (n=5, 522), and patients with chronic CAD from the UCC-SMART cohort (n=5, 308). Individual treatment benefit was expressed as (i) 10-year absolute risk reductions (ARRs) for myocardial infarction, ischemic stroke, or cardiovascular death (MACE), and (ii) life-years gained free of MACE. Predictions were also performed for MACE plus ischemia-driven coronary revascularization (MACE+), through development of a new competing risk-adjusted lifetime prediction model in data from the REACH registry (n=14, 522). Low-dose colchicine was compared to alternative intensive prevention goals, i.e. low density lipoprotein-cholesterol (LDL-c) reduction to <1.4 mmol/L, and systolic blood pressure (SBP) reduction to <130 mmHg. Results: Median individual 10-year ARR for MACE from low-dose colchicine therapy was 4.6% (interquartile range [IQR] 3.6–6.0%), and median gain in life expectancy free of MACE was 2.0 (IQR 1.6–2.5) years. Median 10-year ARR for MACE+ was 8.6% (IQR 7.6–9.8%), and median gain in MACE+-free life expectancy was 3.4 (IQR 2.6–4.2) years. For intensified LDL-c and SBP reduction respectively, median 10-year ARRs were 3.0% (IQR 1.5–5.1%) and 1.7% (IQR 0.0–5.7%) for MACE, and 5.2% (IQR 2.5–8.7%) and 2.9% (IQR 0.0–9.5%) for MACE+. Median life-years gained from LDL-c and SBP reduction were 1.2 (IQR 0.6–2.1) and 0.7 (IQR 0.0–2.3) years free of MACE, and 1.8 (IQR 0.8–3.3) and 0.9 (IQR 0.0–3.4) years free of MACE+. Conclusion: The individual absolute benefit from low-dose colchicine varies between patients. In an era where lipid- and blood pressure-lowering therapies are already routinely used, the benefits of low-dose colchicine are expected to be of at least similar magnitude to those of intensified LDL-c and SBP reduction in patients with chronic CAD. Funding Acknowledgement: Type of funding sources: None.